2017
DOI: 10.1530/joe-17-0289
|View full text |Cite
|
Sign up to set email alerts
|

Stress-responsive HILPDA is necessary for thermoregulation during fasting

Abstract: Hypoxia-Inducible Lipid-Droplet Associated protein (HILPDA) has been shown to localize to lipid droplets in nutrient responsive cell types such as hepatocytes and adipocytes. However, its role in the control of whole-body homeostasis is not known. We sought to measure cell-intrinsic and systemic stress responses in a mouse strain harboring whole body Hilpda deficiency. We generated a genetically engineered mouse model of whole body HILPDA deficiency by replacing the coding HILPDA exon with Luciferase. We subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…HILPDA is a much weaker ATGL inhibitor than the structurally related G0S2 protein in enzymatic assays with purified proteins (32); and we and others have shown that it does not directly regulate lipolysis in adipocytes (24,26,29). It is thus probable that specific upstream stimuli are required for HILPDA activation and/or its weak ATGL inhibitory activity becomes necessary with respect to other lipases and their inhibitors.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…HILPDA is a much weaker ATGL inhibitor than the structurally related G0S2 protein in enzymatic assays with purified proteins (32); and we and others have shown that it does not directly regulate lipolysis in adipocytes (24,26,29). It is thus probable that specific upstream stimuli are required for HILPDA activation and/or its weak ATGL inhibitory activity becomes necessary with respect to other lipases and their inhibitors.…”
Section: Discussionmentioning
confidence: 90%
“…These adaptive functions of HILPDA support the growth of model tumors. HILPDA has been implicated in lipid turnover in mice (24)(25)(26)(27)(28)(29), and recently two independent reports provided evidence of physical interaction between HILPDA and the ratelimiting triglyceride hydrolase ATGL (31,32), which appears to be responsible for its protumorigenic activity (31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations